Soil organic carbon predictions in Subarctic Greenland by visible–near infrared spectroscopy. Issue 1 (1st January 2019) - Ogrič, M.; Knadel, M.; Kristiansen, S. M.; Peng, Y.; De Jonge, L. W.; Adhikari, K.; Greve, M. H.
ABSTRACT: Release of carbon from high-latitude soils to the atmosphere may have significant effects on Earth's climate. In this contribution, we evaluate visible–near-infrared spectroscopy (vis-NIRS) as a time- and cost-efficient tool for assessing soil organic carbon (SOC) concentrations in South Greenland. Soil samples were collected at two sites and analyzed with vis-NIRS. We used partial least square regression (PLS-R) modeling to predict SOC from vis-NIRS spectra referenced against in situ dry combustion measurements. The ability of our approach was validated in three setups: (1) calibration and validation data sets from the same location, (2) calibration and validation data sets from different locations, and (3) the same setup as in (2) with the calibration model enlarged with few samples from the opposite target area. Vis-NIRS predictions were successful in setup 1 ( R 2  = 0.95, root mean square error of prediction [RMSEP] = 1.80 percent and R 2  = 0.82, RMSEP = 0.64 percent). Predictions in setup 2 had higher errors ( R 2  = 0.90, RMSEP = 7.13 percent and R 2  = 0.78, RMSEP = 2.82 percent). In setup 3, the results were again improved ( R 2  = 0.95, RMSEP = 2.03 percent and R 2  = 0.77, RMSEP = 2.14 percent). We conclude that vis-NIRS can obtain good results predicting SOC concentrations across two subarctic ecosystems, when the calibration models are augmented with few samples from the target site. Future efforts should be made toward determination of SOC stocks to constrain soil–atmosphere carbon exchange.